The dynamics of deep water subsea lifting operations in super-harmonic resonance via the harmonic balance method. (November 2021) - Tommasini, Rodrigo Batista; Hill, Thomas L.; Macdonald, John H.G.; Pavanello, Renato; Carvalho, Leonardo de Oliveira
Abstract: The dynamics of deep water subsea lifting operations experiencing super-harmonic resonance is analysed in this study. The harmonic balance method is used to solve the non-dimensional equation of motion of the system and the results are compared with time domain integration and with an equivalent energy dissipation model for typical subsea lifting scenarios. It is demonstrated that 1:3 and 1:5 super-harmonic resonances represent significant features of the response of the system and can lead to large dynamic forces in the cable, which may violate the structural limits of the system in real operations. The harmonic balance method presents results almost as accurate as the time domain integration but up to 25 to 35 times faster, while the equivalent energy dissipation model is not able to represent the super-harmonic resonances. Consequently, taking into account the dynamics introduced by super-harmonic resonances is necessary in the analysis of subsea lifting operations, as it can be the limiting design criterion in certain scenarios, and the harmonic balance method can be used as a fast and accurate method to solve this problem. Highlights: A nonlinear equation of motion is presented to model deep water lifting operations. The Harmonic Balance Method (HBM) is used to efficiently solve this equation. Results obtained using the HBM are validated using time domain integration. Super-harmonic resonances can lead to large dynamic loads in the system. Loads at super-harmonic resonances can reduce the operational weather window.